Analisis Motivasi Belajar Akibat Pandemi Covid-19 pada Siswa Kelas IV SDN Getasblawong Kendal - Aprina Enggar Resty; Asep Ardiyanto; Ferina Agustini (STKIP Andi Matappa Pangkep, 2021)
The background that encourages this research is the decline in student’s learning motivation due to the COVID-19 pandemic. The learning process during the COVID-19 pandemic in Indonesia that implemented by the schools is online learning. This was experienced by one of the schools, namely SD N Getasblawong Kendal. Based on the background above, the purpose of this study is to find out the motivation to learn and what factors that influence learning motivation due to the COVID-19 pandemic in fourth grade students of SD N Getasblawong Kendal.This type of research is qualitative with descriptive methods. The research subjects were 19 students and 1 teacher for grade IV SD N Getasblawong Kendal. Sources of data obtained through observation, interviews, questionnaires and documentation.The results of the analysis of learning motivation due to the COVID-19 pandemic in students showed a percentage of 60.42% or in the medium motivation category. Based on the results of the research, the suggestion that can be conveyed is that students need to be given support from parents and class teachers. The role of parents is very influential on students' learning motivation so that children can increase their learning motivation.